Stress – (self) eating: Epigenetic regulation of autophagy in response to psychological stress. (4th April 2019) - Puri, Deepika; Subramanyam, Deepa
Abstract : Autophagy is a constitutive and cytoprotective catabolic process. Aberrations in autophagy lead to a multitude of degenerative disorders, with neurodegeneration being one of the most widely studied autophagy‐related disorders. While the field has largely been focusing on the cytosolic constituents and processes of autophagy, recent studies are increasingly appreciating the role of chromatin modifications and epigenetic regulation in autophagy maintenance. Autophagy has been implicated in the regulation of neurogenesis, and disruption of neurogenesis in response to psychological stress is a proximal risk factor for development of neuropsychiatric disorders such as major depressive disorder (MDD). In this review, we will discuss the regulation of autophagy in normal neurogenesis as well as during chronic psychological stress, focusing on the epigenetic control of autophagy in these contexts, and also highlight the lacunae in our understanding of this process. The systematic study of these regulatory mechanisms will provide a novel therapeutic strategy, based on the use epigenetic regulators of autophagy to enhance neurogenesis and potentially alleviate stress‐related behavioral disorders. Abstract : Autophagy is a conserved catabolic process, and aberrations in this process lead to numerous degenerative disorders. The regulation of autophagy at the level of chromatin is still underappreciated. This review discusses the epigenetic regulation of autophagy during neurogenesis both in steady state and in response to psychological stress, and proposes the use of epigenetic modulators of autophagy to induce neurogenesis as a novel paradigm to combat the neuropsychological and behavioral effects of stress.